PERCEPTION, ATTITUDE AND PRACTICE OF ENGLISH PRESENTATION SKILLS BY STUDENTS AT THE UNIVERSITY OF DANANG-UNIVERSITY OF FOREIGN LANGUAGE STUDIES (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aimed to find out the perception, attitude, and practice of English presentation skills of first-year English students from the Faculty of Foreign Language Teacher Education and the Faculty of English at The University of Danang-University of Foreign Language Studies (hereafter called EFL students for brief) as well as to propose appropriate solutions to assist them. Data were collected from 200 questionnaires and the analysis of the in-depth interviews was conducted with 10 student informants and observations of 30 students in total. The findings showed that most students were familiar with English presentation skills. Also, they were aware of the importance of presentation skills and agreed on their necessity for a successful presentation. Knowledge was what caused participants the most difficulties during the preparation stage, and when presenting, students struggled the most not to replicate the textbook word-by-word. To solve these problems, several solutions were discussed in the study.